Fundamental Evaluation of Gas-Phase Elementary Reaction Models for Silicon Carbide Chemical Vapor Deposition. (1st January 2017) - Funato, Yuichi; Sato, Noboru; Fukushima, Yasuyuki; Sugiura, Hidetoshi; Momose, Takeshi; Shimogaki, Yukihiro
Abstract : This report verified the existing gas-phase elementary reaction models for chemical vapor deposition (CVD) of silicon carbide (SiC) from methyltrichlorosilane (MTS) developed by Iowa State University (ISU model) and Scientific Research Associates (SRA model). SiC-CVD involves consecutive reactions starting from gas-phase reactions of MTS to form intermediate species, followed by their surface reactions. In this study, the models were verified with respect to the overall decomposition rate constant of MTS ( k MTS ), which was evaluated at 960–1000°C using a quadrupole mass spectrometer (QMS). The relationship between the MTS retention ratio and residence time showed that the overall loss rate of MTS followed first-order kinetics. The obtained k MTS was subsequently divided into the overall gas-phase reaction rate constant ( k g ) and the overall surface reaction rate constant ( k s ) considering the contribution of these two factors by studying reactors with different surface area to volume ( S / V ) ratios. Then, k g was compared with the overall MTS decomposition rate constant calculated from the ISU ( k ISU ) and SRA models ( k SRA ). Neither model reproduced the experimental results exactly, but the inclusion of elementary reactions and gas-phase species may improve their accuracy. The improved model is under construction and will be reported in a future study.